2009
DOI: 10.1149/1.3125285
|View full text |Cite
|
Sign up to set email alerts
|

Water-Stable Lithium Anode with the Three-Layer Construction for Aqueous Lithium–Air Secondary Batteries

Abstract: A water-stable multilayer Li-metal electrode consisting of a lithium metal, a PEO 18 LiN͑SO 2 CF 3 ͒ 2 -BaTiO 3 composite polymer, and a lithium-conducting glass ceramic Li 1.35 Ti 1.75 Al 0.25 P 0.9 Si 0.1 O 12 ͑LTAP͒ was proposed as the lithium anode for aqueous lithium-air secondary batteries. The addition of finely dispersed nanosize BaTiO 3 in the polymer electrolyte greatly reduced the interfacial resistance between the Li anode and the polymer electrolyte. A Li/PEO 18 LiN͑SO 2 CF 3 ͒ 2 -10 wt % BaTiO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 20 publications
3
107
0
2
Order By: Relevance
“…[ 20 , 21 ] Various ionic conducting glass-ceramic protective double layers have been introduced to improve the charge -ransfer reaction of Li ions between Li metal and aqueous electrolytes. [22][23][24][25] The Imanishi group reported that Li 1 + x + y Al x Ti 2-x Si y P 3-y O 12 was stable in water, but is reactive with Li metal. However, a glass-ceramic Li 3-x PO 4-y N y (LiPON) and a lithium-conducting polymer electrolyte (PEO 18 LiTFSI) inhibited the direct reaction of Li and LATP.…”
Section: Confi Guration: Non-aqueous Vs Aqueous Vs Hybrid Vs All-smentioning
confidence: 99%
“…[ 20 , 21 ] Various ionic conducting glass-ceramic protective double layers have been introduced to improve the charge -ransfer reaction of Li ions between Li metal and aqueous electrolytes. [22][23][24][25] The Imanishi group reported that Li 1 + x + y Al x Ti 2-x Si y P 3-y O 12 was stable in water, but is reactive with Li metal. However, a glass-ceramic Li 3-x PO 4-y N y (LiPON) and a lithium-conducting polymer electrolyte (PEO 18 LiTFSI) inhibited the direct reaction of Li and LATP.…”
Section: Confi Guration: Non-aqueous Vs Aqueous Vs Hybrid Vs All-smentioning
confidence: 99%
“…[12][13][14] A PEO film (ca. 300 µm thickness) containing LiTFSI and BaTiO3 was placed between a LTAP glass ceramic (10 mm × 10 mm × 0.15 mm) and lithium foil (5 mm × 5 mm × 0.2 mm).…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
“…[11] The protected Li electrode, which has been developed for use as a negative electrode in Li-Air rechargeable battery, is fabricated by sealing Li metal and a Li-ion conducting solid electrolyte with an aluminum package. [12][13][14] The AdHiCap combines the battery-like redox reaction at the Li negative electrode and capacitive charge storage at the positive electrode, similar to a lithium ion capacitor (LIC), which is a well-known hybrid EC with high cell voltage of ~4 V in non-aqueous electrolytes. [15][16][17] In our previous work, the proof-of-concept of AdHiCap was presented using chemically synthesized MnO2 with acetylene black (AB) as a conductive additive in a beaker-type flooded cell setup.…”
Section: Introductionmentioning
confidence: 99%
“…7, where platinum with platinum black was used as the counter electrode. 21 The cell resistances increased only 10% over one month, which suggests excellent stability of the multilayer Li anode construction in aqueous solution. Using the same equivalent circuit in Fig.…”
Section: Electrode Performance Of the Wslementioning
confidence: 99%